Socialization of Management practices for Sustainable Goat Farming Business: Community Service - Wenny Desty Febrian; Ovi Hamidah Sari (Siber Nusantara Research, 2025)
This community service activity was held on August 15, 2025, in Kampar Regency with 109 participants. The main objective of the activity was to provide outreach to increase public knowledge regarding business procedures in the livestock sector, thereby encouraging the emergence of new entrepreneurs while strengthening the local economic sector. This activity was carried out on agricultural land using a participatory approach through material presentation methods, question and answer discussions, and direct visits to livestock locati mons. The material provided included the basics of livestock business management, livestock product marketing strategies, and challenges and opportunities in the modern livestock industry. Participants were seen enthusiastically participating in the entire series of activities, as evidenced by the many questions and discussions that developed during the interactive session. Through direct visits to livestock locations, participants gained a real picture of the livestock cultivation process and business management that can be applied in their respective regions. The results of this activity showed an increase in participants' understanding of the technical and business aspects of the livestock sector. Thus, this outreach program is expected to be a stimulus for the Kampar Regency community in developing productive, sustainable, and high-economic value livestock businesses.